Formulation and Evaluation of Curcumin Loaded Nanoliposome on Brain Targeted - Jyoti Kumari; Lovely Chaurasia (Current Research in Pharmaceutical Sciences, 2021)
The present work aimed to produce Curcumin based nanoliposomes that nanoliposome can target the site via the brain in a controlled manner. Nanoliposomes are important in controlling the carriage; Curcumin which is an active constituent of curcuminoids thus also provides an effective treatment for the central nervous system and plays a crucial role. The interaction of the drug was ruled out by FT-IR studies and no incompatibility and lipids and surfactant. To optimize the formulation, factors affecting the physical appearance of Nanoliposomes were investigated. Curcumin-loaded Nanoliposomes were formulated using cholesterol by physical dispersion method and characterized for particle size, drug content, stability, production yield. Prepared nanoliposomes gave the better physical, morphological concerning the concentration of the lipids, surfactant, and ratio of lipid and surfactant. Six different formulations of Nanoliposomes F1-F6 were formulated to obtain the optimized formulation. The TEM (Transmission Electron Microscopy) of Nanoliposomes showed that they were rounded in shape and porous in texture. In-vitro drug release of formulation indicates that formulation F6 was selected as an optimized formulation for incorporation into the nanoliposomes among all the six formulations and liposome showed drug release in a controlled manner at the end of 10 hours.